Eleven shades of food integrity: a halal supply chain perspective - Ali, Mohd Helmi; Suleiman, Norhidayah (Elsevier, 2018)
Background: Food integrity is not only related to the good quality of the food product, nonetheless, it distresses closely more on the health, safety, religious and cultural matters. Weaknesses in handling, monitoring, processing and other factors along the food’s supply chain outbreaks the recent food integrity scandal. These outbreak food integrity scandals could be prevented if clear aspects that affect the food integrity were embraced along the food supply chain. This article is aiming to highlight the factors affecting food integrity in the context of the halal food supply chain and their potential for future research. Scope and approach: This review attempts to provide a wider view of supply chain management in the halal food industry. Attention is drawn to the literature on other food industries and the results there are put in the context of the halal food setting. In this review, it emphasizes the factors could be monitor or control that contributes to the problem of food integrity. Key findings and conclusions: Eleven ‘shades’ of food integrity in the halal supply chain are offered, which can be categorized into four supply chain dimensions, related to raw materials, production, service, and the consumer. Each shade is defined and aligned with the results in the literature, and areas for future research are suggested. Theoretical and managerial implications are provided. The ‘shades’ highlighted can be used and considered by managers as fundamental insights to ponder in safeguarding the integrity of halal products.